Evaluation of Performance Characteristics of different Commercially available Diagnostic tests for hepatitis C virus antibodies in major Public Laboratories in Baghdad - Mohammed Ali, Saad H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Immunoassays are one of the oldest techniques used in diagnostic virology where a number of serologic techniques, with different degrees of sensitivity and specificity, for the detection of HCV antigens and their specific antibodies, have been developed.Materials and methods: One hundred and four sera samples were collected from National Center for Blood Transfusion, Gastroenterology and Liver Diseases Hospital, Central Public Health Laboratories and Teaching Laboratories. According to the manufacturers practical instructions, many available methods for detecting Anti-HCV antibodies, including enzyme linked immunosorbent assay (ELISA), immunochromatographic assay (ICA), recombinant immunobloting assay (RIBA), were applied.Results: Although RIBA test is expensive and little bit laborious, this technique proved to be a powerful laboratory technique with both very high sensitivity and specificity when compared to ELISA, since the latter gave false negative results that were found by RIBA to be repeatedly positive. The ICA test for anti- HCV Abs was found to be a test with a relatively comparable sensitivity and specificity results to EIA / ELISA.Conclusion: RIBA is a trustful test in big laboratory centers for anti-HCV Abs screening well with or without ELISA test (if a laboratory personnel are feasible to be available and trained for this purpose).The ICA test for anti-HCV, that need no expensive instrumentation, was found as a rapid, simple and cheaper test that could be used with comparable results to ELISA, for mass screening, at least, in rural laboratory centers.